Model of Community Ecosystem Through Intercropping Pattern of Energy Crops With Design Thinking Approach - Fitria , Rista; Yuliariskha, Fania; Kharisma, Muhammad Faidzdiya Ul Haq; Asep Taryana (Manunggal Halim Jaya, 2025)
Environmental and sustainability issues are currently important in economic activities. One of the widely discussed environmental and sustainability issues is air pollution from coal burning in power plants (PLTU), which is not environmentally friendly or renewable. Besides the benefits felt, especially in electrical energy, it has negative economic, social, and environmental impacts, especially for local communities. Therefore, solutions are needed to minimize the negative impacts. The first three stages of design thinking, empathize, define, and ideate, become the initial stages to validate the ideas generated before further implementation. Literature study results show that idea generation is done using an empathy map in the empathize stage. The empathize stage indicates that handling air pollution from coal burning in PLTU is not yet optimal, causing public anxiety due to the resulting impacts. Therefore, efforts are needed to minimize the negative impacts. The define stage explains that emissions contributed by coal-fired power plants amount to 35%, and the sustainability of coal fuel is still questionable, thus requiring other fuel sources and a concept to obtain this biomass. The ideate stage produces a community ecosystem model through an intercropping pattern of energy crops that offers increased economic, social, and environmental benefits and reduces the negative impacts of air pollution from coal burning.